Upaya Peningkatan Bersihan Jalan Napas Keluarga Tn.B Dengan Tuberkulosis Paru Di Sukoharjo - Ekawati, Ida; , H.M. Abi Muhlisin, SKM., M.Kep (2016)
The TBC disease still become a problem in world's healthy. WHO reported that 0,5% world's inhabitants infected TBC disease, about 75% in developing countries such as in Indonesia that found about 539.000 new cases TB BTA positively with mortality 101.000 every years (Depkes, 2010). Indonesia has occupy in 3rd level after India and China that become a country with most TBC cases. The result of prevalensi survey TBC in Indoneisa in 2009 is about 1,7 million people have death that caused TBC disease (Depkes, 2011). Based on data from Department of healthy in central java show the finding suspect in 2010 that as many as 10.971 people has Tuberculosis. The finding of Tb lungs BTA positively about 82 people (55%). Based on data from Puskesmas Sukoharjo in 2014 that found cases of lungs tuberculosis with BTA positively in Puskesmas Sukoharjo divided into 15 man and 11 woman, whereas for suspect lungs tuberculosis found the result as 187 man and 154 woman (DKK, 2014). The aim of this research is to give treatment on Ny. S who suffer lungs tuberculosis with the uneffectiveness the clean of way breathing problem. The methodology that used in is descriptive method with study cases approach towards treatment on medical patient with lungs tuberculosis begin investigation, diagnose, intervention, implementation, and evaluation. The result that have from postural drainage with effective cought action that used in medical patient success to remove sputum so the way of breathing has clear. The conclution is the problem can handle, the intervention can continue with suggest the family for care the mother intensive and to do postural drainage and cought effectively when the way of breathing disturbed again.